2022
DOI: 10.21272/mmi.2022.1-05
|View full text |Cite
|
Sign up to set email alerts
|

Employee satisfaction and motivation of retail store employees

Abstract: In the 21st century, the rapid technological development in different innovations has not reduced the value of human capital. It is considered to be the most valuable capital of businesses and acts as a driving force of business activity. The perception of human capital should be essential since it has a real impact on the business's success. In human resources management, it is necessary to keep in mind one of the basic functions of management: motivation, planning, and organizing. The main goal of this artic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 38 publications
(43 reference statements)
3
4
0
Order By: Relevance
“…The practical contribution of this paper is reflected in the fact that managers can increase employees' motivation and decrease labor fluctuation which is in accordance with previous researches [49,55,56].…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…The practical contribution of this paper is reflected in the fact that managers can increase employees' motivation and decrease labor fluctuation which is in accordance with previous researches [49,55,56].…”
Section: Discussionsupporting
confidence: 86%
“…These results are similar to the results of the Machová [49] where authors concluded that the most popular motivation tools proved to be the financial incentives in the form of salary increases or bonuses. Poor interpersonal relationships and stressful work greatly affect job change in freight forwarding and logistics companies, which is similar to the results of the Machová [49]. It is very important that the HR service and other sectors pay more attention to this serious problem.…”
Section: Practical and Theoretical Implicationssupporting
confidence: 88%
See 1 more Smart Citation
“…In people management, it is necessary for nurse managers to keep in mind the basic functions of management: motivation, planning, and organisation. With regard to motivation, it should be noted that an adequately motivated professional is key in achieving the organisation’s objectives, since motivation promotes satisfaction, involvement, loyalty and the willingness to do more and do it better [ 30 ]. Thus, it is essential to invest in nurses’ motivation.…”
Section: Discussionmentioning
confidence: 99%
“…safety at work, fair remuneration, social security, and benefits, work climate, basic rights and freedoms, corporate image, and equal opportunity. Based on the results of Machova et al (2022), the most popular motivational tools proved to be financial incentives in the form of salary increases or bonuses. According to Bajrami et al (2021), there is a lack of job security.…”
mentioning
confidence: 99%